Training in Indonesian Language and Literature Teaching Models Based on the National Curriculum for Elementary, Middle, and High School Teachers in Gowa Regency by the Department of Indonesian Literature, Faculty of Cultural Sciences, Hasanuddin Universit: Pelatihan Model Pengajaran Bahasa dan Sastra Indonesia berdasarkan Kurikulum Nasional bagi Guru-Guru SD, SMP, dan SMA/SMK Kab. Gowa oleh Departemen Sastra Indonesia FIB Unhas - Munira Hasjim; Muhammad Nur Iman; AB Takko Bandung; Muslimat, Muslimat; Asriani Abbas; St. Nursa’adah (Universitas Lancang Kuning, 2024)
This training aims to enhance the capabilities of elementary, middle, and high school teachers in Gowa Regency in implementing Indonesian Language and Literature teaching models aligned with the National Curriculum. The problem addressed is the lack of understanding and skills among teachers in applying effective teaching methods that meet curriculum standards. Organized by the Department of Indonesian Literature, Faculty of Cultural Sciences, Hasanuddin University, this training program utilizes a participatory approach involving group discussions, simulations, and teaching practice evaluations. The training results show an improvement in teachers' understanding and ability to design and manage learning processes that meet students' needs and curriculum demands. The positive impact of the program is evident in the increased confidence of teachers in their teaching practices. In conclusion, this training is essential for supporting the quality of Indonesian Language and Literature education in schools and strengthening the effective implementation of the National Curriculum